Association between Weitbrecht's Retinaculum Injury and Femoral Head Necrosis in Femoral Neck Fractures. Issue 8 (11th July 2022) - Mei, Jiong; Wang, Shuqing; Ni, Ming; Zhang, Fangfang; Tang, Jianfei; Bi, Gang; Zhu, Yi; Zhu, Xiaozhong; Lu, Ye
Abstract : Objective: To investigate associations between femoral head necrosis (FHN) and injury to the retinaculum of Weitbrecht in patients with femoral neck fractures who had undergone initial trials of either closed reduction or direct open reduction. Methods: This prospective observational study included 110 patients with displaced femoral neck fractures admitted to the Sixth People's Hospital Affiliated to Shanghai Jiaotong University and Shanghai Tongji Hospital between January 2008 and May 2017. Among these, 25 patients underwent initial closed reductions, and 85 patients underwent an open reduction directly. Watson‐Jones anterolateral approach was used during the surgery for injury to the retinaculum of Weitbrecht, and FHN was assessed as a surgical outcome. The severity of injury to the retinaculum of Weitbrecht was evaluated using a scoring system developed by our surgical team. Follow‐up was at least 24 months. Results: The initial closed reduction treatment group had significantly higher total scores of injury to the retinaculum of Weitbrecht (6.24 ± 2.20 vs 4.62 ± 2.12, p = 0.009) compared to the open reduction group. High total scores were significantly associated with initial trials of closed reduction treatment, especially for the broken and released injury to the superior and anterior retinacula (both p = 0.01). Twenty‐six patients experienced FHN postoperatively, with mean onset time of 19.42 ± 3.87 months. FHN was significantly associated with the severity of injury to the retinaculum of Weitbrecht ( p < 0.001) at the superior, anterior, and inferior retinacula. FHN was significantly associated with injury to the retinaculum of Weitbrecht in females. Conclusions: Femoral neck displacement in patients treated initially with closed reduction is associated with subsequent injury to the retinaculum of Weibrecht, which may lead to FHN. Severity of injury to the retinaculum of Weibrecht may be used as a biomarker to evaluate bone necrosis in patients with femoral neck fractures. Abstract : Femoral head necrosis (FHN) risk was positively associated with Weitbrecht's retinaculum injury in comparison with patients' without FHN. Weitbrecht's retinaculum injury level could be used as a biomarker to evaluate bone necrosis in patients with femoral neck fractures.